X CONGRESO INTERNACIONAL DE FILOSOFÍA APLICADA. PERSPECTIVAS DE PROFESIONALIZACIÓN - de Haas, Leon; Haterlot, Peter (Revista Internacional de Filosofía Aplicada HASER, 2021)
In the summer of 2010, the 10th International Conference on Philosophical Practice (10th ICPP) took place at Leusden, the Netherlands. 120 Practicing philosophers from all over the world participated in world cafés, master classes, and workshops. In this evaluating impression of the conference, the authors will point out and discuss trends and tendencies concerning the professionalization of philosophical practice.